FRAUD AND PROPERTY DAMAGE BY DECEPTIN OR ABUSE OF CONFIDENCE: COMPARATIVE LEGAL ANALYSIS - A. I. Rosentsvayg (Russian Journal of Economics and Law, 2012)
The article presents the comparative analysis of objective and subjective signs of fraud and property damage by deception or abuse of confidence; the similarity and difference features of such property encroachments are viewed; the author suggests uniting the corpus delicti by Articles 159 and 165 of the Russian Criminal Code into the general notion of fraud. The author proves that the novel comprises both misappropriation and acquisition of property right and illegal acquisition of other benefits of property character.